2016
DOI: 10.1016/j.jdermsci.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Paquinimod reduces skin fibrosis in tight skin 1 mice, an experimental model of systemic sclerosis

Abstract: Paquinimod reduces skin fibrosis in an experimental model of SSc, and this effect correlates with local and systemic effects on the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…23 Several studies have suggested that Paquinimod binds Mrp14 protein and disrupts its binding to the proinflammatory receptors (RAGE) and TLR4. A novel report by Yang et al 21 demonstrated that Mrp8/14 upregulated TNF-α and IL-6 expression levels and activated the phosphorylation of NF-κB P65 in mouse macrophages.…”
Section: Platelet-neutrophil Interaction Upregulates Tlr4/myd88/nf-mentioning
confidence: 99%
“…23 Several studies have suggested that Paquinimod binds Mrp14 protein and disrupts its binding to the proinflammatory receptors (RAGE) and TLR4. A novel report by Yang et al 21 demonstrated that Mrp8/14 upregulated TNF-α and IL-6 expression levels and activated the phosphorylation of NF-κB P65 in mouse macrophages.…”
Section: Platelet-neutrophil Interaction Upregulates Tlr4/myd88/nf-mentioning
confidence: 99%
“…The potential mechanism of Pirfenidone is inhibiting the nuclear accumulation of intracellular proteins SMAD2/3 to regulate TGF-β signaling (Choi et al, 2012 ). Other approved inhibitor drugs include Ruxolitinib for bone marrow fibrosis (Wilkins et al, 2013 ), Paquinimod for SSc (Stenstrom et al, 2016 ), and Pentoxifylline (Okunieff et al, 2004 ) combined with vitamin E (Jacobson et al, 2013 ).…”
Section: Drugs and Targets In Fibrosismentioning
confidence: 99%
“…Blockade of S100A8/9 binding to its receptor by administration of Paquinimod was beneficial. Specific inhibition of S100A8/9 by Paquinimod reduced inflammation and pathology under various disease conditions, including leukocyte recruitment during sterile inflammation, experimental systemic sclerosis, and experimental osteoarthritis ( 102 105 ). Therefore, MDSC may represent the S100A8/9-driven connection that links massive neutrophil influx to impaired Th1 immune responses and memory phenotypes thereof.…”
Section: Controlling Th1-supressing Immune Cell Subpopulationsmentioning
confidence: 99%